2019
DOI: 10.5863/1551-6776-24.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Bifidobacterium Species in Prevention of Necrotizing Enterocolitis in Very-Low Birth Weight Infants. A Systematic Review

Abstract: Necrotizing enterocolitis (NEC) is one of the most common and serious gastrointestinal diseases in preterm infants. The aim of this systematic review examines the effects of probiotics on preventing NEC in very-low birth weight (VLBW) infants with a focus on the Bifidobacterium species and its strains. A systematic review of randomized trials and retrospective studies analyzing the use of probiotics to prevent NEC in VLBW infants was conducted using PubMed, Cochrane Central Registry of Controlled Trials, and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 29 publications
0
34
0
2
Order By: Relevance
“…[25][26][27] Deshpande et al, in the meta-analysis they conducted, concluded that probiotics had important benefits in decreasing NEC incidence. 28 Several studies highlighted that bifidobacterium probiotics decreased NEC incidence. 28 Co-citation analysis showed that the researchers mostly cited the studies conducted by Bell et al, Neu and Walker, Walsh and Kliegman, and Lin and Stoll in the reference sections of their articles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27] Deshpande et al, in the meta-analysis they conducted, concluded that probiotics had important benefits in decreasing NEC incidence. 28 Several studies highlighted that bifidobacterium probiotics decreased NEC incidence. 28 Co-citation analysis showed that the researchers mostly cited the studies conducted by Bell et al, Neu and Walker, Walsh and Kliegman, and Lin and Stoll in the reference sections of their articles.…”
Section: Discussionmentioning
confidence: 99%
“…28 Several studies highlighted that bifidobacterium probiotics decreased NEC incidence. 28 Co-citation analysis showed that the researchers mostly cited the studies conducted by Bell et al, Neu and Walker, Walsh and Kliegman, and Lin and Stoll in the reference sections of their articles. [21][22][23] Keyword analysis results showed that probiotics, toll-like receptors 4 (TLR 4), nitric oxide, human milk/breast milk words together with NEC were prominent.…”
Section: Discussionmentioning
confidence: 99%
“…However, few immunonutritional works have been performed so far in preterm neonates; the literature is scarce or even absent in terms of immunomaturation and they are just focused on NEC without considering immune variables. To date, some agents, for example, some Bifidobacterium strains and lactoferrin, have been demonstrated to significantly reduce the incidence of NEC and sepsis in preterm infants, but their impact on the premature immune system has not been evaluated [67,68]. Thus, the present model facilitates the study at preclinical level of the impact of bioactive agents able to promote the immune system development as a first step for future clinical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analyses that focussed on bifidobacterial supplementation found a significant reduction in the incidence of mortality and NEC in preterm infants. 34 In a RCT that included 24 neonates with gastroschisis (probiotics: 12; placebo: 12), 35 significant dysbiosis was noted, and it was partially attenuated by the administration of Bifidobacterium longum subsp. infantis.…”
Section: Discussionmentioning
confidence: 99%